Variants in genes of innate immunity, appetite control and energy metabolism are associated with host cardiometabolic health and gut microbiota composition (2020)
ABSTRACT: Identifying the genetic and non-genetic determinants of obesity and related cardiometabolic dysfunctions is cornerstone for their prevention, treatment, and control. While genetic variants contribute to the cardiometabolic syndrome (CMS), non-genetic factors, such as the gut microbiota, also play key roles. Gut microbiota is intimately associated with CMS and its composition is heritable. However, associations between this microbial community and host genetics are understudied. We contribute filling this gap by genotyping 60 variants in 39 genes of three modules involved in CMS risk, measuring cardiometabolic risk factors, and characterizing gut microbiota in a cohort of 441 Colombians. We hypothesized that CMS risk variants were correlated with detrimental levels of clinical parameters and with the abundance of disease-associated microbes. We found several polymorphisms in genes of innate immunity, appetite control, and energy metabolism that were associated with metabolic dysregulation and microbiota composition; the associations between host genetics and cardiometabolic health were independent of the participants' gut microbiota, and those between polymorphisms and gut microbes were independent of the CMS risk. Associations were also independent of the host genetic ancestry, diet and lifestyle. Most microbes explaining genetic-microbiota associations belonged to the families Lachnospiraceae and Ruminococcaceae. Multiple CMS risk alleles were correlated with increased abundance of beneficial microbiota, suggesting that the phenotypic outcome of the evaluated variants might depend upon the genetic background of the studied population and its environmental context. Our results provide additional evidence that the gut microbiota is under the host genetic control and present pathways of host-microbe interactions.